Post-exercise adipose tissue and skeletal muscle lipid metabolism in humans: the effects of exercise intensity - AL Mulla, Nariman (Blackwell Science Inc, 2000)
1. One purpose of the present experiments was to examine whether the relative workload or the absolute work performed is the major determinant of the lipid mobilization from adipose tissue during exercise. A second purpose was to determine the co-ordination of skeletal muscle and adipose tissue lipid metabolism during a 3 h post-exercise period. 2. Six subjects were studied twice. In one experiment, they exercised for 90 min at 40 % of maximal O(2) consumption (V̇(O(2), max)) and in the other experiment they exercised at 60% V̇(O(2), max) for 60 min. For both experiments, catheters were inserted in an artery, a subcutaneous abdominal vein and a femoral vein. Adipose tissue metabolism and skeletal muscle (leg) metabolism were measured using Fick's principle. 3. The results show that the lipolytic rate in adipose tissue during exercise was the same in each experiment. Post-exercise, there was a very fast decrease in lipolysis, but it began to increase about 1 h post-exercise and remained elevated for the following 2 h. The increase in post-exercise non-esterified fatty acid (NEFA) mobilization was greater after 60 % exercise than after 40 % exercise. 4. It is concluded that the lipolytic rate in abdominal subcutaneous adipose tissue during exercise is the same whether the relative workload is 40 % or 60 % of maximum. Post-exercise, there is a substantial lipid mobilization from adipose tissue and only a small fraction of this is taken up in the lower extremities. This leaves a substantial amount of NEFAs for either NEFA/TAG (triacylglycerol) recirculation post-exercise or immediate oxidation.